2014
DOI: 10.1111/imj.12375
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based prescribing of drugs for secondary prevention of acute coronary syndrome in Aboriginal and non‐Aboriginal patients admitted to Western Australian hospitals

Abstract: Opportunity exists to improve prescribing of recommended drugs for ACS patients at discharge from WA hospitals in both Aboriginal and non-Aboriginal patients. Attention regarding pharmaceutical management post-ACS is particularly required for patients from rural and remote areas, and those attending district and private hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…The significantly reduced participation in tertiary prevention following stroke in the indigenous population is likely to have a wide‐ranging impact on the health system and the individual . Length of stay following stroke is decreasing due to improvements in acute management .…”
Section: Discussionmentioning
confidence: 99%
“…The significantly reduced participation in tertiary prevention following stroke in the indigenous population is likely to have a wide‐ranging impact on the health system and the individual . Length of stay following stroke is decreasing due to improvements in acute management .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified lower rates of evidence-based prescribing during hospitalization in more remote areas 14 and have identified physician specialty and hospital geographic region as independent predictors of evidence-based medical therapy prescription at discharge. 15 In our study, hospital and physician characteristics were important predictors of antiplatelet agent and statin use at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…After this adjustment, the rates and type of intervention (including PCI and CABG surgery) during an ACS event were identical 98 . Similarly, the adjusted rates of evidence‐based prescribing for post‐hospital secondary prevention were similar in Aboriginal and non‐Aboriginal patients 99 …”
Section: Aboriginal and Torres Strait Islander Peoplementioning
confidence: 91%